Reformulation of Digital Market Regulations Against Indications of Monopolistic Practices in the Digital Spaces (Indonesian Perspective) - Muliani, Alisya; Sukarmi, Sukarmi; Djumikasih, Djumikasih (IJBLE Scientific Publications Community Inc., 2024)
This research aims to analyze indications of monopolistic practices in the digital space and find formulations for digital market regulation to create a fairer digital ecosystem. Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition does not yet specifically regulate the prohibition of monopolistic practices and unfair business competition in the digital space, so the incompleteness of this regulation needs to be investigated further. This research was conducted using a normative juridical approach. The results of this research show that indications of monopolistic practices in the digital space are related to the unclear categories of business actors who sell at a loss in e-commerce and the combination of social media and e-commerce. Based on these weaknesses, the author obtains a formulation based on the Digital Markets Act regulations in the European Union which creates